Reconfiguração de redes de distribuição em regime normal de operação utilizando o Software Opendss - Bacin, Pedro (2019)
Technical losses in distribution networks are an important measure of efficiency in the electric sector, they are inevitable and are responsible for dissipating a considerable portion of the energy injected into the system. Network reconfiguration techniques allow topology changes under normal operation, as it enables reducing technical losses from load balancing between feeders, resulting in improved power quality indicators. These techniques are increasingly being used due to the growth of smart grids and remote-controlled equipment in distribution networks. In 2014, ANEEL established OpenDSS as the software to be used for loss calculation in distribution system through load flow methodology. The OpenDSS is an free software that works in open source which can be customized by programming to the user’s needs and allows the use of COM interface in association with other softwares. Thus, in this work, the energy losses acquisition under normal operation were performed in daily analyzes and, subsequently, in analyzes with reconfigurations from the opening and closing of switches at defined load levels. For these topology changes, was used basic network reconfiguration techniques in a base system using some modifications, based on the assumptions of the branch-exchange method. Despite the occurrence of some limitations in the application of the method, significant reductions in losses were observed with its use for the studied cases.